Investigation of the Relationship between Science Burnout Levels and Test Anxiety of Secondary School Students According to Some Variables - Namudar İzzet Kurbanoğlu; Berrin Nur Zor; Sefa Yüce (Sakarya University Journal of Education)
In thisstudy, it has been investigated whether there is a significant relationshipbetween the science course burnout and test anxiety scores of the secondaryschool students in the teaching process. In addition, it was investigatedwhether the burnout and test anxiety scores of the students in the sciencecourse differed according to gender. Burnout and test anxiety for sciencecourse scales were used in the study as data collection tools. The universe ofthis study is composed of students who study at secondary schools in thecentral districts of Sakarya. The sample consists of a total of 641 students,298 girls (46%) and 343 boys (54%), attending six different state secondaryschools in the central districts. Research hypotheses were analyzed with“Speraman Correlation” and “Mann-Whitney U” because the data were notdistributed normally. The results showed that there was a positive andsignificant relationship between the students' burnout scores and the testscores. Moreover, while the students' science course burnout scores differedstatistically according to their gender (p<.05), the test scores did notshow a statistically significant difference (p>.05).In thisstudy, it has been investigated whether there is a significant relationshipbetween the science course burnout and test anxiety scores of the secondaryschool students in the teaching process. In addition, it was investigatedwhether the burnout and test anxiety scores of the students in the sciencecourse differed according to gender. Burnout and test anxiety for sciencecourse scales were used in the study as data collection tools. The universe ofthis study is composed of students who study at secondary schools in thecentral districts of Sakarya. The sample consists of a total of 641 students,298 girls (46%) and 343 boys (54%), attending six different state secondaryschools in the central districts. Research hypotheses were analyzed with“Speraman Correlation” and “Mann-Whitney U” because the data were notdistributed normally. The results showed that there was a positive andsignificant relationship between the students' burnout scores and the testscores. Moreover, while the students' science course burnout scores differedstatistically according to their gender (p<.05), the test scores did notshow a statistically significant difference (p>.05).